A real-world pharmacovigilance analysis of the risk of retinal artery occlusion from medication use - Andrew Mihalache; Ryan S. Huang; Marko M. Popovic; Kirill Zaslavsky; David Sarraf; SriniVas R. Sadda; Rajeev H. Muni; Edward A. Margolin (AJO International)
Purpose: The risk of retinal artery occlusion (RAO) as related to specific drug use is unclear. Using the Food and Drug Administration Adverse Event Reporting System (FAERS), we aimed to comprehensively elicit a list of FDA-approved drugs overreported for RAO. Design: Retrospective, population-based pharmacovigilance study. Methods: Pharmacovigilance data were sourced from the FAERS database between October 2003 and March 2024 using Open Vigil 2.1 (Kiel, Germany) software. FDA-approved pharmacological agents which were recorded as the primary suspect drug for at least 10 reports of RAO were included. Disproportionality analyses were performed to identify positive adverse drug reaction signals by comparing drug-specific reports of RAO to the background rate of RAO reports across all other drugs in the database. Results: Out of 12,345,128 adverse events reported to the FAERS database during the study period, 1,461 (0.01 %) were identified as cases of RAO. Most primary suspect drugs were indicated for eye disorders (20.7 %, n = 303/1,461), neoplasms (11.4 %, n = 166/1,461), or musculoskeletal and connective tissue disorders (7.2 %, n = 105/1,461). Notably, brolucizumab and tranexamic acid were significantly overreported for RAO events. These were followed by melphalan, triamcinolone, aflibercept, ranibizumab, lidocaine, sildenafil, epinephrine, bupivacaine, and rofecoxib. Conclusion: Several primary suspect drugs showed disproportionately high reports of RAO in the FAERS database; however, some of these medications are indicated for conditions associated with a hypercoagulable state, a significant risk factor for RAO. These findings underscore the need for continued pharmacovigilance efforts to distinguish potential drug-related effects from the influence of underlying disease.